O Banco Mundial e as políticas públicas para a reforma agrária de mercado no Triângulo Mineiro/Alto Paranaíba – 2000 a 2017 - Freitas, Ricardo Luis de (2020)
This present thesis aims to analyze the investment programs carried out by the World Bank group in Brazil, focused on strategic departments such as the agribusiness and the management of natural resources, performed through land credit programs. In order to achieve the research objectives, we applied a combination of qualitative methods, including the theoretical review, field research, analysis of contents, Mind Maps, data collection from primary and secondary sources. By analyzing the investment mechanisms performed in Brazil, we highlight the participation of interest groups and the State in enabling the application of financial activities in this country. We have researched their participation in water and forests sector, as well for the infrastructure sector in Brazil, in the development of programs and resources allocation, in partnership with State representatives. Through loan agreements settled in several countries, new strategies were developed in order to expand these activities to new sectors and regions. In this context, our research object refers to the Land Bank project, implemented in the mesoregion of Triângulo Mineiro/Alto Paranaíba (2001), consisting in a program developed under the influence of the Rural Caucus, in support of land privatization and promoting the abandonment of the Agrarian Reform model promoted by the State. Several aspects contributed to the establishment of the Market Assisted Land Reform – RAM (in Portuguese) as a complementary policy for land access, in order to inhibit the land occupations carried out by socioterritorial movements. Despite reducing social conflicts, the land credit programs aimed to defend a private property model in agriculture, maintaining the land concentration structure, which is a prevailing aspect in Brazil. The family farmers who had access to this policy, aimed the debt repayment, although some associations were not able to comply with their debts, resulting in deep social consequences. Hence, this research demonstrates the investment panorama performed by the World Bank group in Brazil, focusing on the ventures established in the mesoregion of Triângulo Mineiro/Alto Paranaíba.